2020
DOI: 10.1155/2020/2483435
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Circulating Fetuin-B Levels Are Associated with Insulin Resistance and Reduced by GLP-1RA in Newly Diagnosed PCOS Women

Abstract: Background. Previous studies have suggested that Fetuin-B seems to be a secreted adipokine related to metabolic diseases. However, the results have been inconsistent. Here, our objective is to investigate the changes in circulating Fetuin-B levels in women with polycystic ovary syndrome (PCOS) and analyze the association of Fetuin-B and insulin resistance (IR). Methods. The current study is comprised of a cross-sectional study and a series of interventional studies. Oral glucose tolerance test (OGTT) and eugly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…FBLN1 is abundant in the plasma and arterial walls of patients with type 2 diabetes and can be used as a predictor of cardiovascular mortality in patients with type 2 diabetes [41]. An independent risk factor for type 2 diabetes is the plasma levels of AHSG, which is an insulin receptor inhibitor secreted by the liver and, along with FETUB [42,43], thought to be an important factor in insulin resistance in obesity [44,45]. GPLD1 serves as a biomarker that effectively differentiates latent autoimmune diabetes in adults from type 2 diabetes in the early stage [46], and it was shown that the circulating GPLD1 concentration in diabetic rats could be restored to normal levels by exercise training [47].…”
Section: Discussionmentioning
confidence: 99%
“…FBLN1 is abundant in the plasma and arterial walls of patients with type 2 diabetes and can be used as a predictor of cardiovascular mortality in patients with type 2 diabetes [41]. An independent risk factor for type 2 diabetes is the plasma levels of AHSG, which is an insulin receptor inhibitor secreted by the liver and, along with FETUB [42,43], thought to be an important factor in insulin resistance in obesity [44,45]. GPLD1 serves as a biomarker that effectively differentiates latent autoimmune diabetes in adults from type 2 diabetes in the early stage [46], and it was shown that the circulating GPLD1 concentration in diabetic rats could be restored to normal levels by exercise training [47].…”
Section: Discussionmentioning
confidence: 99%
“…Untargeted proteomic analysis also enables the identification of interesting novel targets for future research. Fetuin-B is a relatively understudied hepatokine associated with insulin resistance, dyslipidemia, and non-alcoholic fatty liver disease ( Meex and Watt, 2017 ; Mokou et al , 2020 ; Olkowicz et al , 2021 ). Serum levels of fetuin-B increase during pregnancy but normalize after delivery ( Šimják et al , 2018 ), possibly related to hormonal changes of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing our OGTT results, we can see that the glycemia is also much higher in rats fed with the HSF diet before or after the DJOS surgery. Mokou et al [ 28 ], in their study on women with polycystic ovarian syndrome (PCOS), showed elevated levels of fetuin-B in the serum of the studied subjects. Moreover, they found that fetuin-B concentration in the serum was even higher in obese subjects when compared with those without this comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that fetuin-B concentration in the serum was even higher in obese subjects when compared with those without this comorbidity. Therefore, they suggested that fetuin-B might be associated with indicators of lipid and glucose metabolism and markers of inflammation [ 28 ]. On the other hand, Xing et al [ 29 ] reported that the elevated levels of fetuin-B could be at least partly associated with the higher risk of myocardium ischemia.…”
Section: Discussionmentioning
confidence: 99%